The Strategic Role of Non-Judicial Mediators in Achieving Effective and Just Family Dispute Resolution in the Batam Religious Court - Jalili, Ahmad; Nabila, Dachia; Andriansyah, Muhammad (Jurnal El-Thawalib, 2025)
This research is motivated by the increasing number of family cases at the Batam Religious Court and the need for mediation as a more effective and equitable alternative dispute resolution. The purpose of this study is to analyze the contribution of non-judgmental mediators in resolving family conflicts and to identify the role, challenges, and effectiveness of mediation. This is a qualitative field study. Primary data were collected through in-depth interviews with non-judgmental mediators, judges, and litigants at the Batam Religious Court, while secondary data were obtained from annual reports, mediation documents, and literature on religious court mediation. Data collection techniques included observation, interviews, and documentation, while data analysis used a descriptive-analytical approach to examine the contribution patterns and effectiveness of non-judgmental mediation in resolving family conflicts. The results show that non-judgmental mediators have a strategic role in facilitating peace through a more humanistic, flexible, and deliberation-based communication approach. Their presence can reduce judges' caseloads, accelerate settlement, and maintain harmonious family relations after the conflict. Despite obstacles such as low public legal awareness, resistance from disputing parties, and a limited number of certified mediators, the effectiveness of mediation by non-judge mediators has been quite high, with a positive impact on the just, peaceful, and sustainable resolution of family cases.